DESIGN OF EFFICIENT BCD ADDERS IN QUANTUM-DOT CELLULAR AUTOMATA USING VERILOG - RADHIKA.R (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
DESIGN OF EFFICIENT BCD ADDERS IN QUANTUM-DOT CELLULAR AUTOMATA USING VERILOG